EMPOWERING SHARIA SECURITIES: IMPLEMENTING AN ISSUERS' MENTORING PROGRAM FOR LOSS MITIGATION IN CROWDFUNDING - KAMIL, MUH. AHSAN; RIVA'I, YAHYA (Al-Masraf: Jurnal Lembaga Keuangan dan Perbankan, 2023)
This study aims to implement a mentoring program for issuers (MSMEs) in sharia securities crowdfunding in Indonesia to mitigate the losses. A qualitative approach was used, using in-depth literature studies with relevant stakeholders and analyzing secondary data. The data was then analyzed by reducing data, displaying data and verifying. The research findings highlight that in the Sharia securities crowdfunding mechanism, the organizer only functions as a platform that brings together investors and issuers. Therefore, in this research, the author recommends a mentoring program for MSME issuers that organizers of Sharia crowdfunding securities can implement. This recommendation is based on the general weaknesses of MSMEs, which can cause the risk of losses and defaults. With this mentoring program, it is hoped that publishers' businesses can avoid the risk of loss and continue to grow to benefit all parties.